SOME ASPECTS OF FINANCIAL ANALYSIS ACCORDING TO REPORTING INDICATORS - HARAKOZ, LILYA; FELONIUK, OLHA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
An important characteristic of the functioning of any economy is its stability, which expresses the ability of the economic system of the country to resist, adapt and recover from the effects of negative external influences. Timely response of the system to the changes taking place can help reduce the severity of the crisis situation and increase its resilience. The aim of the work is to study the definition of theoretical aspects of the stability of the economic system and the disclosure of factors that affect it. The article reveals the concept of system as a general scientific concept, which is defined as a set of interconnected and properly arranged elements of a particular holistic formation. The concept of economic system is defined as a set of interconnected and appropriately ordered elements of the economy that form a certain integrity, the economic structure of society, which has a common goal. The views of various scholars on the interpretation of the concept of sustainability are analyzed, and a generalized definition is established as the ability of the system to independently maintain balance between the components of the internal environment under the influence of external influences. The groups of systemic stability, which are inherent in socio-economic regional systems, have been studied. Factors that may affect the economic stability of systems are considered. It was found that the task of maintaining the stability of the system is to use the complex interdependence of various factors and processes, to launch mechanisms of self-organization and bring the system on the trajectory of sustainable operation and development. Assessing the impact of factors on the stability of the economic system can be done using the analysis of indicators that relate to both external and internal environment. Alan Limited Liability Company was selected to carry out the analysis of industrial economic stability. Based on the data of the financial statements, the calculation of stability at the enterprise level was carried out and the level of probability of bankruptcy of the considered company was investigated. The authors’ opinion on the transformation of Ukraine’s economic model from export-oriented to foreign-sustainable is studied, for which one of the steps should be the development and implementation of the State Strategy for Internal Market Development.